Monopoli Lada dan Emas di Pantai Barat Sumatera: Konflik Internal Melayu dan Intervensi VOC dalam Narasi Hulubalang Raja Karya Nur Sutan Iskandar - Moh Atikurrahman; Meiyra Nur Laili; M. Ridwan (Jurnal Tamaddun, 2022)
In the Indonesia-centrism historiography devide et impera is generally understood as the intrigue of the colonizer to dominate the archipelago. Vereenigde Oostindische Compagnie (VOC)'s cunning tactic is related to the colonialism of abundant natural resources in the archipelago. The historical narrative that emerged was that the VOC was accused of being the ringleader of dividing the nation in order to smooth out the ambitions of monopoly on spices and other commodities. The European Meneer was labeled as an antagonist who maneuvered in order to control the maritime trade network of the archipelago. On the other hand, in historical reconstruction, trade competition between brothers and/or local rulers tends to be ignored. In fact, their conflict (internal Malay) is more entrenched, massive, and latent. This article aims to explore medieval primordial conflicts along the West Coast of Sumatra. As a narrative balance, the novel Nur Sutan Iskandar, which takes the background from 1665-1668, is examined because it offers an alternative discourse about a dramatic chronicle between traders and rulers of Aceh and Minangkabau. In modern Indonesian literature, Hulubalang Raja (1934) is known as a historical literary work. From the perspective of New Historism, the conflict between Raja Adil and Hulubalang Raja is a representation of the Malay people. The colossal conflict between the Malays is understood as the author's literary strategy to trick Balai Pustaka's censorship. In addition, the text of the story can also be interpreted as a message to the readers of the 30s decade who are experiencing contractions to realize the idea of a nation-state which will later be called "Indonesia". Instead of cornering the Kompeni, the main problems of the people of the archipelago at that time were exposed through colossal conflicts between the nation's children. In the romance narrative of the Balai Pustaka tradition, the dominant narrative is the internal conflict of the Malay. Meanwhile, the double storylines of the shortcut novels seem confusing and incoherent. However, the fictional building was related to the repression of the colonial side through Balai Pustaka which aggressively censored, tightened, and banned books that were considered subversive to the power of the Dutch East Indies.